Answer:
(x+y)=`(`x*`y)
Step-by-step explanation:
We have to apply some properties of logic gates (as involution and DeMorgan's law) in order to get the answer:
![`(`x)=x\\and\\`(x+y)=`x*`y](https://img.qammunity.org/2020/formulas/computers-and-technology/college/qr12z220dw4vjh0vj7zhzoei1bd4ijj9dl.png)
applying the last two properties:
![(x+y)=`(`(x+y))\\(x+y)=`(`x*`y)](https://img.qammunity.org/2020/formulas/computers-and-technology/college/gumyml358i6vh9yrievokkk2ajo893pv1c.png)
So if we negate x and y, multiply them and then negate them again, it will be equal to a logic sum.